Towards Open-Source Cloud Adoption : Exploring the Determinants - Chirchir P. K,; Muhambe T. M,; Obare E. O, (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2024)
The trends in cloud computing development have become fundamental building blocks to many business information system models and innovations, the architects are designing cloud systems to be as effective and beneficial as possible. In this paradigm, open-source cloud platforms are part of the design philosophy that drives innovation in cloud services. The adoption of open-source cloud has become pervasive in the modern enterprise; this has been accelerated by perceived benefits of openness. The power in the community of developers and openness fosters development of hardened, secure and reliable solutions. These features enable a collaborative source code, modification and customization geared towards innovation with positive impact on the design, aligning perfectly with the dynamic nature of open-source cloud solutions. However, the slow adoption rate in the modern enterprises has been attributed to a lack of understanding of open-source cloud adoption. This study explores the determinants of open-source cloud adoption in the context of higher learning institutions. A deductive thematic analysis technique was utilized in the study.
Keywords: Grid; Openness; Open-Source Cloud; Proprietary Cloud; Serverless; Source-Code; Web 4.0